2005
DOI: 10.1111/j.1523-1755.2005.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of information from single versus multiple frequency bioimpedance vector analysis in hemodialysis

Abstract: From high Xc values at low frequency, tissue anisotropy is inferred. Intra- and extracellular current flow causes equivalence of information based on functions of R and Xc measurements made at 50 kHz versus other frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 39 publications
1
52
0
1
Order By: Relevance
“…(19). Actually, several approaches to DW prediction and to optimization of fluid removal during HD using BIA have been shown to be successful (2,(11)(12)(13); furthermore, very recently, an equivalence of information in fluid monitoring during HD, using measurements at 50 Khz, conventional series circuit, versus bioimpedance spectroscopy with Cole and Hanai model was demonstrated (20). Therefore, the answer to the question of whether technology (BIA) can solve the clinical problem of DW is definitely yes, as outlined by Schneditz in a very recent editorial comment (21): ".…”
Section: Discussionmentioning
confidence: 99%
“…(19). Actually, several approaches to DW prediction and to optimization of fluid removal during HD using BIA have been shown to be successful (2,(11)(12)(13); furthermore, very recently, an equivalence of information in fluid monitoring during HD, using measurements at 50 Khz, conventional series circuit, versus bioimpedance spectroscopy with Cole and Hanai model was demonstrated (20). Therefore, the answer to the question of whether technology (BIA) can solve the clinical problem of DW is definitely yes, as outlined by Schneditz in a very recent editorial comment (21): ".…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that altered tissue composition leads to changes in the impedance locus, e.g. displacement, contraction, enlargement or rotation, which are reflected by the parameters of the Cole model [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we reported the use of single frequency BIA in determining the nutritional and hydration status of the patient as well as survival prediction [7,[25][26][27]. We suggest further exploration in regard to resistive and capacitive indices [25,26] and extension of research into haemodialysis [28], HIV [29] and other diseases and healthy control populations.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest further exploration in regard to resistive and capacitive indices [25,26] and extension of research into haemodialysis [28], HIV [29] and other diseases and healthy control populations. Certainly further study is needed to reaffirm the clinical role of BCI and CH 2 .…”
Section: Discussionmentioning
confidence: 99%